Buying And Selling Transactions At The People's Market Selimbau District Kapuas Hulu Regency According To Islamic Economics - Agus Salim; Munadi; Deni Irawan (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
This research is motivated by the development of the Times which is characterized by economic development that is increasingly rapid, causing higher business competition. With such high competition, business people can use all means to make a profit. Deviant behavior is often found in traditional markets, among others: reduction of the measure of the scales, good quality goods with poor quality, and also there are some traders when serving buyers do not behave friendly or generous with marked service with a less friendly face. So that researchers want to know more about the application of buying and selling transactions in traditional markets according to Islamic Economics. The focus of the problem of this study is about the application, implementation, constraints, solutions of buying and selling transactions in traditional markets Islamic economic perspective. While the purpose of this study is to explain, identify and solutions for the application of buying and selling transactions in traditional markets Islamic economic perspective. The research approach is qualitative research and types using phenomenology. The number of informants from this study there are 6 traders, 6 buyers around the market and 2 market managers. Methods of data collection by observation, interviews and documentation. Technical analysis using the Miles and Huberman models. Checking the validity of the data by triangulation. The research stages consist of preparation, implementation and data analysis stages. The results of research on the first problem, in the application of buying and selling transactions are not in accordance with the principles according to Islamic Economics, and there is still fraud in the scales and service traders to buyers who are still less maintain silahturahim well. Second, the constraints that occur in both research sites are still not in accordance with the principles of Islamic Economics. Because there is one merchant who has practiced usury, has broken his promise in ordering goods, and has committed fraud. Third, solutions to reduce constraints include cooperation with BPOM. Monitor activities on a scale of goods available at the Selimbau Sub-District People's market. Conduct periodic monitoring of each trader and the location of other markets. Conduct market operations and receive complaints from buyers or traders in case of problems. Then orderly in supervising every scales, the price of goods and quality sold in the market traders Selimbau District People's market